Kalappia celebica, an endemic wood from Sulawesi Island: Chemical composition and its resistance against white rot fungi Ganoderma tsugae and G. lucidium. Issue 1 (November 2021) - Pujirahayu, Niken; Arif, Asrianti; Uslinawaty, Zakiah; Ibrahim, Nurhayati Hadjar; Bakara, Waode Erniwati; Megawati,; Syahidah,
Abstract: Kalapi wood ( Kalappia celebica kosterm) is endemic to Sulawesi Island and is a monotype species in the Fabaceae family with limited distribution. This study investigates the chemical composition and natural durability of Kalapi ( K. celebica Kosterm) wood against white rot fungi Ganoderma tsugae and G. lucidium. This study was conducted based on the TAPPI standard for moisture analysis content, ASTM-D for extractive content, holocelluloce, and lignin, and method Cross and Bevan for cellulose. Durability observation was conducted in 12 weeks by assessing the percentage damage of wood samples caused by the fungi according to SNI standards 01-7207-2014. Results show that K. celebica has holocelullose, cellulose, and extractives at a high level, lignin was moderate, and had low hemicellulose. The results of testing the durability of wood shown that K. celebica has resistance to G. tsugae attack (class II) but is not resistant to G. lucidium (class IV), with an average weight loss of 3.14 % and 18.82 %, respectively.